Magnetic resonance findings of Stewart–Treves Syndrome in primary limb lymphedema compared with pathology: A retrospective single-center study - Li, Bin; Li, Jiyuan; Hao, Kun; Jin, Yanfang; Ma, Jun; Du, Xuemei (Frontiers in Oncology, 2023)
Background Stewart–Treves Syndrome in Primary Limb Lymphedema (STS-PLE) is an extremely rare malignant tumor. A retrospective analysis was conducted to elucidate the relationship between magnetic resonance imaging (MRI) findings and signs compared to pathology. Methods Seven patients with STS-PLE were enrolled at Beijing Shijitan Hospital, Capital Medical University, from June 2008 to March 2022. All cases were examined by MRI. The surgical specimens were subjected to histopathological and immunohistochemical staining for CD31, CD34, D2-40, and Ki-67. Results There were two different types of MRI findings. One was mass shape (STS-PLE I type) in three male patients, and the other was the “trash ice” d sign (STS-PLE II type) observed in four female patients. The average duration of lymphedema (DL) of STS-PLE I type (18 months) was shorter than that of STS-PLE II type (31 months). The prognosis for the STS-PLE I type was worse than that for the STS-PLE II type. Regarding overall survival (OS), the STS-PLE I type (17.3 months) was three times shorter than that of the STS-PLE II type (54.5 months). For STS-PLE I type, the older the STS-PLE onset, the shorter the OS. However, there was no significant correlation in STS-PLE II type. MRI was compared to histological results to provide an explanation for the differences in MR signal changes, especially on T2WI. Against a background of dense tumor cells, the richer the lumen of immature vessels and clefts, the higher the T2WI MRI signal (taking muscle signal as the internal reference standard) and the worse the prognosis, and vice versa. We also found that younger patients with a lower Ki-67 index (<16%) had better OS, especially for the STS-PLE I type. Those with stronger positive expression of CD31 or CD34 had shorter OS. However, the expression of D2-40 was positive in nearly all cases, and seemed not to be associated with prognosis. Conclusions In lymphedema, the richer the lumen of immature vessels and clefts based on dense tumor cells, the higher the T2WI signal on the MRI. In adolescent patients, the tumor often showed a “trash ice” sign (STS-PLE II-type) and prognosis was better than for the STS-PLE I type. While in middle-aged and older patients, tumors showed a mass shape (STS-PLE I type). The expression of immunohistochemical indicators (CD31, CD34, and KI-67) correlated with clinical prognosis, especially decreased Ki-67 expression. In this study, we determined it was possible to predict prognosis comparing MRI findings with pathological results.